Modeling and Simulation the Effect of Welding Current and Welding Time on Welding Joint Stresses - سلامة, احمد; سلوم, تمام (Latakia University Journal -Engineering Sciences Series, 2021)
In this study, modeling and simulation was performed using the Finite element method (FEM )terminated method on the CATIA V5 program for a welding connection at welding currents (80, 100, 110, 120) amps and different welding times (6, 7, 8) seconds and the results showed that at a welding current of 110 amps For a period of 6 seconds, the distribution of heat stress was better through the diameter and depth of the welding zone. As the results obtained using the CATIA V5 program were compared with the results of reference studies in this field and using different programs.